BN-Cu current collector and application thereof in zinc ion battery

By growing hexagonal boron nitride film on pure copper foil, BN-Cu current collector was prepared, which solved the problem of easy corrosion of traditional pure copper current collectors, and significantly improved the cycle life and Coulomb efficiency of zinc ion batteries.

CN119650706APending Publication Date: 2025-03-18ANHUI UNIV

Patent Information

Application Number
CN202411861400.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional pure copper current collectors are prone to corrosion in zinc ion batteries, resulting in short battery cycle life and low Coulomb efficiency, and the prior art cannot effectively process or protect copper current collectors.

Method used

A continuous hexagonal boron nitride film was grown on pure copper foil by chemical vapor deposition method to prepare a BN-Cu current collector. The method includes polishing pure copper foil, building a model and performing chemical vapor deposition on it.

Benefits of technology

BN-Cu current collector effectively inhibits zinc dendrites growth, improves zinc ion migration, improves battery life, reduces corrosion reactions, enhances Coulomb efficiency, and provides good mechanical support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650706A_ABST
    Figure CN119650706A_ABST
Patent Text Reader

Abstract

The invention discloses a BN-Cu current collector and application thereof in a zinc ion battery. A preparation method of the BN-Cu current collector comprises the following steps: (1) polishing pure copper foil; (2) the polished pure copper foil is placed on a square crucible, and a pure copper foil-square quartz plate-pure copper foil model is built on the crucible; and (3) taking ammonia borane as a precursor, taking the pure copper foil-square quartz plate-pure copper foil model as a substrate, and growing a continuous hexagonal boron nitride film on the pure copper foil by adopting a chemical vapor deposition method to obtain the BN-Cu current collector. The BN-Cu current collector can promote zinc ion migration, so that the problems of dendritic crystal growth, hydrogen evolution reaction and the like existing in a zinc negative electrode at present are solved, zinc dendritic crystals can be effectively inhibited, and the service life of a battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery current collectors, and in particular to a BN-Cu current collector and application thereof in a zinc ion battery. Background Art

[0002] Zinc-ion batteries have attracted widespread attention due to their advantages such as high safety, abundant resources and environmental protection. However, due to the unstable chemical properties of pure copper, easy reaction with electrolytes and easy galvanic corrosion with other metals, the traditional pure copper current collector is prone to corrosion during the battery cycle, resulting in a short battery cycle life and reduced electrochemical performance. In the existing battery manufacturing process technology, it is impossible to effectively treat or protect the surface of the copper current collector, so that the copper current collector has been contaminated or damaged to a certain extent during the battery assembly process, and is more prone to corrosion in the subsequent cycle process, resulting in a relatively low cycle life and coulomb efficiency of the pure copper current collector. Therefore, it is of great practical value to develop a new type of zinc-ion battery current collector material to improve battery cyclability and efficiency. Summary of the invention

[0003] The object of the present invention is to provide a BN-Cu current collector and its application in a zinc ion battery, which can solve the problems existing in the prior art such as uncontrollable growth of zinc dendrites, low coulombic efficiency, excessive use of metallic zinc and low energy density.

[0004] In one aspect of the present invention, the present invention provides a method for preparing a BN-Cu current collector. According to an embodiment of the present invention, the method comprises the following steps:

[0005] (1) Polishing the pure copper foil;

[0006] (2) placing the polished pure copper foil on a square crucible, and building a pure copper foil-square quartz sheet-pure copper foil model on the crucible;

[0007] (3) Using ammonia borane as a precursor and a pure copper foil-square quartz sheet-pure copper foil model as a substrate, a continuous hexagonal boron nitride film is grown on the pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector.

[0008] In addition, the method for preparing a BN-Cu current collector according to the above embodiment of the present invention may also have the following additional technical features:

[0009] In some embodiments of the present invention, in step (1), the polishing liquid used for polishing includes deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea, and the molar ratio of the deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is (10-20): (5-10): (1-5): (0.2-1): (0.032-0.16).

[0010] In some embodiments of the present invention, the polishing voltage is 1-3V, the current is 0.25-0.27A, and the polishing time is 6-10min.

[0011] In some embodiments of the present invention, the size of the square quartz plate is (0.5-1) cm×(0.5-1) cm×(0.5-1) mm.

[0012] In some embodiments of the present invention, in step (3), the specific steps of the chemical vapor deposition method are as follows: placing an ammonia borane precursor at the inlet of the tube furnace, and coating the outer wall of the tube furnace at this location with a heating belt to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; placing a constructed pure copper foil-square quartz sheet-pure copper foil model in the heating zone; and subjecting the pure copper foil-square quartz sheet-pure copper foil to chemical vapor deposition treatment in the presence of a protective gas.

[0013] In some embodiments of the present invention, the protective gas is argon and hydrogen, the gas flow ratio of argon and hydrogen is (20-50): (5-30), the chemical vapor deposition growth time is 1h, the growth temperature of the chemical vapor deposition is 950-1050°C, and the heating zone temperature is 92-98°C.

[0014] In some embodiments of the present invention, in step (3), the amount of ammonia borane added is 15-25 mg.

[0015] In another aspect of the present invention, the present invention provides a BN-Cu current collector prepared according to the preparation method of the BN-Cu current collector. According to an embodiment of the present invention, the thickness of the BN-Cu current collector is 1-2 mm.

[0016] In another aspect of the present invention, the present invention proposes an application of the BN-Cu current collector in a negative electrode current collector of a zinc ion battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1) The BN-Cu current collector of the present invention can promote the migration of zinc ions, thereby improving the problems of dendrite growth and hydrogen evolution reaction currently existing in the zinc negative electrode, and can effectively inhibit zinc dendrites and improve battery life.

[0019] 2) The hexagonal boron nitride on the top of the BN-Cu current collector not only has excellent thermal stability and chemical inertness, but also exhibits excellent electronic insulation, which can effectively prevent the corrosion reaction between zinc ions and copper foil, thereby preventing Zn 2+ Deposited on its surface, reducing the desolvation barrier and promoting Zn 2+ migrate.

[0020] 3) The unique layered structure of the BN-Cu current collector makes the transport of ions in the battery more efficient and provides good mechanical support for the battery.

[0021] 4) The Cu substrate grown on boron nitride has a strong zinc affinity, which promotes the uniform deposition of zinc under the BN layer and in the middle layer of the Cu substrate.

[0022] 5) The BN-Cu current collector anode effectively inhibits the generation of "dead zinc" and accelerates the Zn 2+ The transmission of ZnO increases the stability of aqueous Zn-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XRD pattern of the BN-Cu current collector after zinc is deposited in Application Example 2 of the present invention;

[0024] Figure 2 This is a SEM image of the BN-Cu current collector after zinc is deposited in Application Example 2 of the present invention;

[0025] Figure 3 The Tafel diagrams of the BN-Cu current collector after zinc deposition and the copper after zinc deposition in Application Example 2 of the present invention;

[0026] Figure 4 This is a cycle life diagram of a symmetrical battery assembled with a BN-Cu current collector after zinc deposition and a copper current collector after zinc deposition in Application Example 2 of the present invention;

[0027] Figure 5 This is a coulombic efficiency diagram of a zinc-copper half-cell assembled with a BN-Cu current collector after zinc deposition and copper after zinc deposition in Application Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A method for preparing a BN-Cu current collector comprises the following steps:

[0031] (1) Polish the pure copper foil. Prepare a polishing liquid consisting of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea. The molar ratio of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is 10:5:5:1:0.16. Use a circular pure copper foil with a diameter of 14 mm and a thickness of 1 mm as the anode and a platinum foil as the cathode. Perform electrochemical polishing for 6 minutes at an applied DC voltage of 3 V and a current of 0.25 A. After polishing, rinse the copper foil repeatedly with deionized water and place the cleaned copper foil in anhydrous ethanol for later use.

[0032] (2) Place the polished pure copper foil on a rectangular crucible and build a pure copper foil-square quartz sheet-pure copper foil model on the rectangular crucible. The model is built with a structure in which the first layer is a round pure copper foil, the second layer is a 1 cm × 1 cm × 1 mm quartz sheet, and the third layer is a round pure copper foil.

[0033] (3) Ammonia borane is used as a precursor, and a pure copper foil-square quartz sheet-pure copper foil model built on a rectangular crucible is used as a substrate to grow a continuous hexagonal boron nitride film on the pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector. Specifically, 20 mg of ammonia borane precursor is placed 15 cm away from the air inlet of the tube furnace, and a heating belt is coated on the outer wall of the tube furnace at this location to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; the built pure copper foil-square quartz sheet-pure copper foil model substrate is placed in the heating zone 80 cm away from the air inlet of the tube furnace; under the conditions of a protective gas flow rate of Ar:H2=20sccm:3sccm and a precursor sublimation temperature of 98°C, chemical vapor deposition is performed on the pure copper foil-square quartz sheet-pure copper foil at 1050°C for 1h to obtain a BN-Cu current collector.

[0034] Example 2

[0035] A method for preparing a BN-Cu current collector comprises the following steps:

[0036] (1) Polishing the pure copper foil. Prepare a polishing solution consisting of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea. The molar ratio of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is 10:10:5:1:0.16. Use a circular pure copper foil with a diameter of 14 mm and a thickness of 1 mm as the anode and a platinum foil as the cathode. Perform electrochemical polishing for 6 min at an applied DC voltage of 3 V and a current of 0.25 A. After polishing, rinse the copper foil repeatedly with deionized water and place the cleaned copper foil in anhydrous ethanol for later use.

[0037] (2) Place the polished pure copper foil on a rectangular crucible and build a pure copper foil-square quartz sheet-pure copper foil model on the rectangular crucible. The model is built with a structure in which the first layer is a round pure copper foil, the second layer is a 1 cm × 1 cm × 1 mm quartz sheet, and the third layer is a round pure copper foil.

[0038] (3) Ammonia borane was used as a precursor, and a pure copper foil-square quartz sheet-pure copper foil model built on a rectangular crucible was used as a substrate to grow a continuous hexagonal boron nitride film on pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector. 20 mg of ammonia borane precursor was placed 15 cm away from the air inlet of the tube furnace, and a heating belt was wrapped around the tube wall of the tube furnace at this location to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; the built pure copper foil-square quartz sheet-pure copper foil model substrate was placed in the heating zone 80 cm away from the air inlet of the tube furnace; the pure copper foil-square quartz sheet-pure copper foil was chemically vapor deposited for 1 h at 1050°C under the conditions of a protective gas flow rate of Ar:H2=20sccm:3sccm and a precursor sublimation temperature of 98°C to obtain a BN-Cu current collector.

[0039] Example 3

[0040] A method for preparing a BN-Cu current collector comprises the following steps:

[0041] (1) Polishing the pure copper foil. Prepare a polishing solution consisting of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea. The molar ratio of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is 10:5:5:1:0.16. Use a circular pure copper foil with a diameter of 14 mm and a thickness of 1 mm as the anode and a platinum foil as the cathode. Perform electrochemical polishing for 6 minutes at an applied DC voltage of 3 V and a current of 0.25 A. After polishing, rinse the copper foil repeatedly with deionized water and place the cleaned copper foil in anhydrous ethanol for later use.

[0042] (2) Place the polished pure copper foil on a rectangular crucible and build a pure copper foil-square quartz sheet-pure copper foil model on the rectangular crucible. The model is built with a structure in which the first layer is a round pure copper foil, the second layer is a 1 cm × 1 cm × 1 mm quartz sheet, and the third layer is a round pure copper foil.

[0043] (3) Ammonia borane was used as a precursor, and a pure copper foil-square quartz sheet-pure copper foil model built on a rectangular crucible was used as a substrate to grow a continuous hexagonal boron nitride film on pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector. 20 mg of ammonia borane precursor was placed 15 cm away from the air inlet of the tube furnace, and a heating belt was wrapped around the tube wall of the tube furnace at this location to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; the built pure copper foil-square quartz sheet-pure copper foil model substrate was placed in the heating zone 80 cm away from the air inlet of the tube furnace; the pure copper foil-square quartz sheet-pure copper foil was chemically vapor deposited for 1 h at 1050°C under the conditions of a protective gas flow rate of Ar:H2=4sccm:1sccm and a precursor sublimation temperature of 98°C to obtain a BN-Cu current collector.

[0044] Example 4

[0045] A method for preparing a BN-Cu current collector comprises the following steps:

[0046] (1) Polishing the pure copper foil. Polish the pure copper foil. Prepare a polishing solution consisting of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea. The molar ratio of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is 10:5:5:1:0.16. Use a circular pure copper foil with a diameter of 14 mm and a thickness of 1 mm as the anode and a platinum foil as the cathode. Perform electrochemical polishing for 6 minutes at an applied DC voltage of 3 V and a current of 0.25 A. After polishing, rinse the copper foil repeatedly with deionized water and place the cleaned copper foil in anhydrous ethanol for later use.

[0047] (2) Place the polished pure copper foil on a rectangular crucible and build a pure copper foil-square quartz sheet-pure copper foil model on the rectangular crucible. The model is built with a structure in which the first layer is a round pure copper foil, the second layer is a 1 cm × 1 cm × 1 mm quartz sheet, and the third layer is a round pure copper foil.

[0048] (3) Ammonia borane was used as a precursor, and a pure copper foil-square quartz sheet-pure copper foil model built on a rectangular crucible was used as a substrate to grow a continuous hexagonal boron nitride film on pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector. 20 mg of ammonia borane precursor was placed 15 cm away from the air inlet of the tube furnace, and a heating belt was wrapped around the tube wall of the tube furnace at this location to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; the built pure copper foil-square quartz sheet-pure copper foil model substrate was placed in the heating zone 80 cm away from the air inlet of the tube furnace; the pure copper foil-square quartz sheet-pure copper foil was chemically vapor deposited for 1 h at 1050°C under the conditions of a protective gas flow rate of Ar:H2=20sccm:3sccm and a precursor sublimation temperature of 92°C to obtain a BN-Cu current collector.

[0049] Example 5

[0050] A method for preparing a BN-Cu current collector comprises the following steps:

[0051] (1) Polishing the pure copper foil. Polish the pure copper foil. Prepare a polishing solution consisting of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea. The molar ratio of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is 10:5:5:1:0.16. Use a circular pure copper foil with a diameter of 14 mm and a thickness of 1 mm as the anode and a platinum foil as the cathode. Perform electrochemical polishing for 6 minutes at an applied DC voltage of 3 V and a current of 0.25 A. After polishing, rinse the copper foil repeatedly with deionized water and place the cleaned copper foil in anhydrous ethanol for later use.

[0052] (2) Place the polished pure copper foil on a rectangular crucible and build a pure copper foil-square quartz sheet-pure copper foil model on the rectangular crucible. The model is built with a structure in which the first layer is a round pure copper foil, the second layer is a 1 cm × 1 cm × 1 mm quartz sheet, and the third layer is a round pure copper foil.

[0053] (3) Ammonia borane was used as a precursor, and a pure copper foil-square quartz sheet-pure copper foil model built on a rectangular crucible was used as a substrate to grow a continuous hexagonal boron nitride film on pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector. 20 mg of ammonia borane precursor was placed 15 cm away from the air inlet of the tube furnace, and a heating belt was wrapped around the tube wall of the tube furnace at this location to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; the built pure copper foil-square quartz sheet-pure copper foil model substrate was placed in the heating zone 80 cm away from the air inlet of the tube furnace; the pure copper foil-square quartz sheet-pure copper foil was chemically vapor deposited for 1 h at 950°C under the conditions of a protective gas flow rate of Ar:H2=20sccm:3sccm and a precursor sublimation temperature of 98°C to obtain a BN-Cu current collector.

[0054] Example 6

[0055] A method for preparing a BN-Cu current collector comprises the following steps:

[0056] (1) Polishing the pure copper foil. Polish the pure copper foil. Prepare a polishing solution consisting of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea. The molar ratio of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is 10:5:5:1:0.16. Use a circular pure copper foil with a diameter of 14 mm and a thickness of 1 mm as the anode and a platinum foil as the cathode. Perform electrochemical polishing for 6 minutes at an applied DC voltage of 3 V and a current of 0.25 A. After polishing, rinse the copper foil repeatedly with deionized water and place the cleaned copper foil in anhydrous ethanol for later use.

[0057] (2) Place the polished pure copper foil on a rectangular crucible and build a pure copper foil-square quartz sheet-pure copper foil model on the rectangular crucible. The model is built with a structure in which the first layer is a round pure copper foil, the second layer is a 1 cm × 1 cm × 1 mm quartz sheet, and the third layer is a round pure copper foil.

[0058] (3) Ammonia borane was used as a precursor, and a pure copper foil-square quartz sheet-pure copper foil model built on a rectangular crucible was used as a substrate to grow a continuous hexagonal boron nitride film on pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector. 20 mg of ammonia borane precursor was placed 15 cm away from the air inlet of the tube furnace, and a heating belt was wrapped around the tube wall of the tube furnace at this location to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; the built pure copper foil-square quartz sheet-pure copper foil model substrate was placed in the heating zone 80 cm away from the air inlet of the tube furnace; under the conditions of a protective gas flow rate of Ar:H2=20sccm:3sccm and a precursor sublimation temperature of 98°C, chemical vapor deposition was performed on the pure copper foil-square quartz sheet-pure copper foil at 1050°C for 40 minutes to obtain a BN-Cu current collector.

[0059] Example 7

[0060] A method for preparing a BN-Cu current collector comprises the following steps:

[0061] (1) Polishing the pure copper foil. Polish the pure copper foil. Prepare a polishing solution consisting of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea. The molar ratio of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is 10:5:5:1:0.16. Use a circular pure copper foil with a diameter of 14 mm and a thickness of 1 mm as the anode and a platinum foil as the cathode. Perform electrochemical polishing for 6 minutes at an applied DC voltage of 3 V and a current of 0.25 A. After polishing, rinse the copper foil repeatedly with deionized water and place the cleaned copper foil in anhydrous ethanol for later use.

[0062] (2) Place the polished pure copper foil on a rectangular crucible and build a pure copper foil-square quartz sheet-pure copper foil model on the rectangular crucible. The model is built with a structure in which the first layer is a round pure copper foil, the second layer is a 1 cm × 1 cm × 1 mm quartz sheet, and the third layer is a round pure copper foil.

[0063] (3) Ammonia borane was used as a precursor, and a pure copper foil-square quartz sheet-pure copper foil model built on a rectangular crucible was used as a substrate to grow a continuous hexagonal boron nitride film on pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector. 20 mg of ammonia borane precursor was placed 15 cm away from the air inlet of the tube furnace, and a heating belt was wrapped around the tube wall of the tube furnace at this location to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; the built pure copper foil-square quartz sheet-pure copper foil model substrate was placed in the heating zone 80 cm away from the air inlet of the tube furnace; the pure copper foil-square quartz sheet-pure copper foil was chemically vapor deposited for 1 h at 1050°C under the conditions of a protective gas flow rate of Ar:H2=20sccm:3sccm and a precursor sublimation temperature of 98°C to obtain a BN-Cu current collector.

[0064] Comparative Example

[0065] Polish the pure copper foil. Prepare a polishing liquid, which is composed of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea. The molar ratio of deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is 10:5:5:1:0.16. Use a circular pure copper foil with a diameter of 14 mm and a thickness of 1 mm as the anode and a platinum foil as the cathode. Perform electrochemical polishing for 6 minutes at an applied DC voltage of 3 V and a current of 0.25 A. After polishing, rinse the copper foil repeatedly with deionized water, and place the cleaned copper foil in anhydrous ethanol for standby use.

[0066] Application Example 1

[0067] Assembly of zinc-copper half-cell: The BN-Cu current collector prepared in Example 1 and the polished pure copper foil prepared in the comparative example are used as the positive electrode, the zinc foil is used as the negative electrode, and the separator is a glass fiber group to assemble the zinc-copper half-cell.

[0068] The above assembled battery was subjected to a coulombic efficiency test, and the parameters for testing the coulombic efficiency were: a discharge current of 3.078 mA, a discharge time of 0.5 h, a charge current of 3.078 A, and a charge voltage of 0.5 V.

[0069] like Figure 5 As shown, the battery maintains high and stable efficiency during operation, further demonstrating the superiority of the BN-Cu current collector.

[0070] Application Example 2

[0071] The assembly of the zinc-copper symmetrical battery includes the following steps:

[0072] (1) Preparation of BN-Zn-Cu electrode sheet

[0073] The BN-Cu current collector prepared in Example 1 and the polished pure copper foil prepared in the comparative example were used as the positive electrode, the zinc foil was used as the negative electrode, the glass fiber was used as the separator, and the 2M zinc sulfate aqueous solution was used as the electrolyte to assemble the battery. 2 The BN-Zn-Cu electrode sheet and the Zn-Cu electrode sheet were obtained by deposition at a current density of 40 min. After the reaction was completed, the BN-Zn-Cu electrode sheet and the Zn-Cu electrode sheet were repeatedly rinsed with deionized water.

[0074] (2) A symmetrical battery was assembled using a BN-Zn-Cu electrode sheet and a Zn-Cu electrode sheet as the positive and negative electrodes, respectively. The electrolyte was a 2M zinc sulfate aqueous solution and the separator was glass fiber.

[0075] The battery assembled above was subjected to a cycle test with the following test cycle parameters: charge and discharge current of 1.5393 mA and charge and discharge time of 1 h.

[0076] like Figure 1 As shown in the XRD diagram of the BN-Cu current collector after zinc deposition, no impurity peaks appear, and the zinc peak is obvious, indicating that the product is of high purity. Figure 2 As shown in the SEM image of the BN-Zn-Cu electrode containing the BN-Cu current collector after zinc deposition, the sample surface is smooth and no obvious zinc dendrites appear. Figure 3 As shown, the corrosion potential of the BN-Zn-Cu electrode containing the BN-Cu current collector after zinc deposition is higher than that of the Zn-Cu electrode sheet after zinc deposition, and the corrosion current density is lower than that of the Zn-Cu electrode sheet after zinc deposition, indicating that the hydrogen evolution reaction is effectively suppressed.

[0077] like Figure 4 As shown, compared with the comparative Zn-Cu electrode sheet, when the BN-Cu current collector is used, the voltage remains stable during the cycle, indicating that the dendrite growth is effectively suppressed.

[0078] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a BN-Cu current collector, characterized in that: The following steps are involved: (1) Polishing the pure copper foil; (2) placing the polished pure copper foil on a crucible, and building a pure copper foil-square quartz sheet-pure copper foil model on the crucible; (3) Using ammonia borane as a precursor and a pure copper foil-square quartz sheet-pure copper foil model as a substrate, a continuous hexagonal boron nitride film is grown on the pure copper foil by chemical vapor deposition to obtain a BN-Cu current collector.

2. The method for preparing a BN-Cu current collector according to claim 1, characterized in that: In step (1), the polishing liquid used for polishing includes deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea, and the molar ratio of the deionized water, anhydrous ethanol, phosphoric acid, isopropanol, and urea is (10-20): (5-10): (1-5): (0.2-1): (0.032-0.16).

3. The method for preparing a BN-Cu current collector according to claim 1, characterized in that: In step (1), the polishing voltage is 1-3V, the current is 0.25-0.27A, and the polishing time is 6-10min.

4. The method for preparing a BN-Cu current collector according to claim 1, characterized in that: In step (2), the size of the square quartz plate is (0.5-1) cm×(0.5-1) cm×(0.5-1) mm.

5. The method for preparing a BN-Cu current collector according to claim 1, characterized in that: In step (3), the specific steps of the chemical vapor deposition method are as follows: placing an ammonia borane precursor at the inlet of the tube furnace, and covering the outer wall of the tube furnace at this location with a heating belt to evaporate the precursor into a boron source and a nitrogen source to reach the substrate during the growth stage; placing a constructed pure copper foil-square quartz sheet-pure copper foil model in the heating zone; and subjecting the pure copper foil-square quartz sheet-pure copper foil to a chemical vapor deposition treatment in the presence of a protective gas.

6. The method for preparing a BN-Cu current collector according to claim 5, characterized in that: The protective gas is argon and hydrogen, the gas flow ratio of argon and hydrogen is (20-50): (5-30), the chemical vapor deposition growth time is 1 hour, the growth temperature of the chemical vapor deposition is 950-1050°C, and the heating zone temperature is 92-98°C.

7. The method for preparing a BN-Cu current collector according to claim 1, characterized in that: In step (3), the amount of ammonia borane added is 15-25 mg.

8. A BN-Cu current collector prepared by the method for preparing a BN-Cu current collector according to any one of claims 1 to 7, characterized in that: The thickness of the BN-Cu current collector is 1-2 mm.

9. Use of the BN-Cu current collector according to claim 8 in a negative electrode current collector of a zinc ion battery.

Citation Information

Patent Citations

  • Method for preparing wafer-level uniform hexagonal boron nitride film

    CN111826712A

  • Method for preparing hexagonal boron nitride film through chemical vapor deposition under normal pressure

    CN115613130A

  • Negative electrode current collector and metal battery comprising same

    CN117882221A

  • Anode current collector and metal battery comprising same

    US20240113305A1

Cited By

  • Bipolar current collector and preparation method and application thereof

    CN121172148A